Institutional Network Model in the Coordination of Street Vendor Empowerment in Makassar City, South Sulawesi, Indonesia - Abdul Mahsyar; Rijal Rijal (Jurnal Ilmiah Ilmu Administrasi Publik, 2021)
The management of street vendors that interferes with city governance has not been effective because it is sporadically done by the displacement or seizure of trading facilities. The pattern is thus ineffective in its construction because it does not reduce the amount, nor the behavior of the street vendors. This research aims to determine the pattern of coaching and explore the model of handling the use of street vendors through a synergic approach between agencies in coordination.  This study uses descriptive type with a qualitative approach. The research site is the location of the street vendors trade in the city of Makassar, the research informant consists of the street vendors, government officials, and public citizens. Data is collected through direct interviews with an informant, field observations, and document analysis. Data analysis is done at the same time when collecting data using the interactive models of Huberman and Miles is data collection, data reduction, display data, and conclusion drawing and verifying. Data, source, and time triangulating data. The results showed the construction of the street vendors still oriented to the regulatory offenders and carried out partially by the agency according to its interests so that the handling has not synergized between government agencies and other related parties. Construction of street vendors is institutionally implemented by sub-district offices and assisted by Makassar public order police, while for the utilization of street vendors needed a model coordinated centrally by the mayor to be structured, programmatic, and integrated so that the street vendors can be empowered and contribute to the development of the city.